VISUALISASI LIRIK LAGU“SENANDUNG” NONARIA DALAM SENI GRAFIS - Putri, Kinanti; Kurniawati, Dyah Yuni (Texture: Visual Art and Culture Journal, 2024)
This article is an expression and visualization of the author's imagination toward the song NonaRia into the form of a high-print graphic artwork. NonaRia is a female duo music group from Indonesia that debuted in 2012 with the genre of jazz swing music. NonaRia's songs have simple and witty lyrics but have deep meanings. Each song has its own magnetic power that seeps into the soul and is engraved in the listener's memory. The interpretationofthemeaningofthelyricsofthesongcontainedinthelyricsof thesong"Senandung"byNonaRiarepresentsadeepsenseofgratitude.The result of thisstudyisto analyze thegraphic elements andthemeaningofthe lyrics of NonaRia's songs into the form of high-print graphic art creations.